CONSTITUTIONAL PHENOTYPING OF ACIDUM PHOSPHORICUM IN TYPE 2 DIABETES MELLITUS: A PROSPECTIVE COHORT STUDY : Constitutional Phenotyping of Acidum Phosphoricum in T2DM - DR. NITESH KUMAR M. BABARIYA,; DR. ANKIT DUBEY, (The Bioscan, 2026)
Type 2 Diabetes Mellitus (T2DM) is influenced by metabolic, neuroendocrine and psychological factors. This prospective exploratory cohort study developed a structured constitutional phenotyping model (Total Acidum Phosphoricum Assessment Score, TAPAS) derived from classical homeopathic literature and explored its association with glycemic trends. Thirty adults with T2DM were followed for six months. Participants meeting predefined phenotypic criteria (TAPAS ≥12 with at least two major traits) received adjunctive Acidum Phosphoricum 30C while continuing stable conventional therapy. Twenty-five participants qualified for the phenotype. Mean HbA1c decreased from 9.03±0.92% to 7.82±0.96%, with a mean reduction of 1.21% (95% CI 0.87–1.55; p<0.001). TAPAS scores showed a moderate positive correlation with HbA1c reduction (r=0.46; p=0.01). Exploratory regression analysis suggested persistence of this association after adjustment for baseline variables. The findings demonstrate the feasibility of operational constitutional phenotyping and its measurable association with glycemic trends in T2DM. The results are hypothesis- generating and support further validation through larger randomized studies.